Soil Physical Properties Affect Herbivory of Lampronadata cristata in a Cork Oak Forest - Xinliang Shao; Xinjuan Zhou; Lin Wang; Ruxue Tan; Can Lu; Qin Zhang; Kedong Xu (Ecology and Evolution, 2024)
ABSTRACT Studies have reported the important role of soil properties in regulating insect herbivory under controlled conditions or at relatively large scales. However, whether fine‐scale variation of soil properties affects insect herbivory under natural conditions in forests is still unclear. We selected a ca. 300 ha Quercus variabilis forest area where the leaf damage was mainly caused by Lampronadata cristata (Lepidoptera: Notodontidae) and set 200 10 × 10 m plots within the area. We examined insect herbivory (percent leaf area damaged) on Q. variabilis and correlated it to soil properties and tree characteristics. Insect herbivory decreased with soil sand percentage and bulk density and increased with DBH and tree height. Effects of soil sand percentage and bulk density on insect herbivory were partly mediated by DBH and tree height. Our results indicated that soil physical properties may have significant effects on insect herbivory by directly influencing insect herbivores that need to complete their life cycle in the soil, or by indirectly affecting insect herbivores through influencing DBH and tree height which reflects the total leaf biomass available to the insect herbivore. This study may help to understand the complex relationship between soil and plant–insect interactions in forest ecosystems.